HIV transmission to transmission to premature very low birth weight infants - Levin, Candyce (Department of Paediatrics and Child Health, 2021)
There is sparse literature about HIV transmission in preterm infants. Eighty-two HIV-exposed preterm infants received birth polymerase chain reactions (PCRs). Five (6.1%) were HIV positive with all 5 mothers receiving inadequate antiretrovirals. Of the PCRnegative infants, 9 died and 87% of the survivors received further PCR testing which remained negative. With correct care, intrapartum transmission of HIV can virtually be eliminated.